Formulation Development and Evaluation of Tablet in Tablet Dosage form to Proffer a Quick and Protracted Relief in Gastritis and Allied Gastric Disorders (Asian Journal of Pharmaceutics (AJP), 2023)
Purpose: The contemporary investigation was intended to extend and appraise uniqueness of the tablet in tabletformulation with a perception to proffer a quick and protracted relief in gastritis and allied gastric disorders.Materials and Methods: The possible drug-excipient interaction between Esomeprazole Magnesium andformulation constituents/excipients of core and outer tablet was envisaged to map the batch composition formulasfor the core tablets. The core tablets were compressed using 6.5 mm die punch (concave) set and outer tablets(devoiding core tablet) were compressed using 14 mm die punch (concave) set with optimized compression loadand speed. Based on performance outcome of core tablet and outer tablet batches, during the assessment of thepost compression parameters, three batches for tablet in tablet were purposed and compacted, which were latersubjected to in vitro release kinetics. The short-term accelerated stability testing of the varied batches of tablet intablet formulations was executed to predict the environmental influence over the quality of finalized formulationand to ensure that no alteration has been brought in to the formulation during the course of manufacturing processthat could negatively impact its stability. The optimized tablet in tablet formulation was compared with thecommercially accessible enteric coated Esomeprazole tablet. The maximum plasma concentration (Cmax, μg/mL)and the corresponding time (Tmax, hour) for the two treatments in each rabbit were estimated through highperformanceliquid chromatography in the plasma concentration data. Results: The post-compression parametersof the core tablets revealed that the CT-26 batch, comprising polyethylene glycol as binder and sodium starchglycolate as disintegrant, was best among rest, of all the batches (CT-1 to CT-27), with crushing strength of 3.57± 0.115 kg/cm2, Friability 0.188 ± 0.002 (% loss), disintegration time of 52.66 ± 0.57 s, and % drug contentwas found to be 100.31 ± 0.32. The post-compression parameters of outer tablet, reveals that the OT-2 batch,comprising microcrystalline cellulose as disintegrant, was best among rest, out of all batches (OT-1 to OT-9), withcrushing strength of 5.55 ± 0.132 kg/cm2, Friability 0.098 ± 0.004 (% loss), and disintegration time of 161.33± 0.57 s. The analysis of the entire tablet in tablet (T in T-1 to T in T-3) batches reveals that of the T in T -3(comprising of CT-26 and OT-2) was the best batch, among rest of all batches (T in T-1 to T in T-3), with meanweight 776.95 ± 0.394 mg, thickness 6.516 ± 0.028 mm, crushing strength of 6.10 ± 0.276 kg/cm2, Friability 0.193± 0.006 (% loss), disintegration time of 189.33 ± 0.577 s, and % drug content 97.36 ± 0.07. The in vitro release ofEsomeprazole magnesium from varied tablet in tablet formulations were also assessed by integrating drug releasestatistics into diverse release pharmacokinetics models. The maximized regression values (0.991) for tablet intablet formulations demonstrated the sensible linearity through Higuchi pharmacokinetic model, signifying theformulations as modified release formulation.The accelerated stability studies have demonstrated the consistentsunset yellow color of the optimized formulation, with smooth surface exclusive of any flaws or cracks. Thedisintegration time of 195.21 ± 1.468 s, and % drug content was found to be 96.79 ± 0.53Conclusion: In the present study, the tablet in tablettechnology was used to formulate an immediate release formulation, in which Esomeprazole Magnesium; an acid labile drugwas kept in core tablet and the outer tablet confining acid neutralizing agents. The constituents of core tablet and outer tabletrelease simultaneously in the stomach acidic environment. The outer tablet containing acid neutralizing agents counterbalancethe gastric environment and thus providing favorable pH environment for the release of esomeprazole in stomach. Both theconstituents act in synergy to produce desired pharmacological action. This will provide instantaneous relief with the release ofacid neutralizing agents from the outer tablet and proffer prolong relief (with the release of esomeprazole from the core table)from the gastric symptoms due to irreversible binding to cysteine residues of the H+/K +ATPase. The clinical action of each drugcomponent will not alter and exhibited their action in synergy. This will offer better therapeutic efficacy and improve patientcompliance.